The impact of coastal upwelling on coral reef ecosystem under anthropogenic influence: Coral reef community and its response to environmental factors - Zhu, Wentao; Ren, Yuxiao; Liu, Xiangbo; Huang, Duanjie; Xia, Jingquan; Zhu, Ming; Yin, Hongyang; Chen, Rouwen; Li, Xiubao (Frontiers in Marine Science, 2022)
Mass coral bleaching is a severe threat to coral reefs in the era of global warming, and upwelling areas may serve as thermal refugia for coral reefs by mitigating the effects of heating anomalies. This study seeks to examine the impact of the Qiongdong upwelling (QDU) on the coastal coral reefs of the Hainan Island. The environmental variables (i.e., physiochemical parameters, coastal land use) differed significantly in upwelling and non-upwelling areas. In particular, the presence of colder and more saline water was the important indicator of coastal upwelling. In the QDU, turf algae and macroalgae dominated the algae communities, but habitat-specific environment and coastal development contributed to lower calcified algae, coral larvae replenishment and live corals cover. Lower abundance of coral reefs fishes at upwelling stations could be attributed to the disappearance of live corals, increase of algae coverage, low habitat complexity and strong wave exposure. Upwelling-related environmental parameters, wave exposure, land use and potential local stressors were revealed as major driving factors related to significant spatial changes in stony coral and fish communities. Overall, the present findings suggest that the Qiongdong upwelling has the potential to provide thermal refuge for coral reefs, but is severely affected by local anthropogenic activities.